A Better Approach to After-Action Reviews - and Fletcher, Angus; Cline, Preston B.; Hoffman, Matthew (Harvard Business Review, 2023)
In the decades since the Army created the After Action Review (AAR), businesses have embraced the practice as a way of learning from both failure and success. But all too often the practice gets reduced to nothing more than a pro forma exercise. The authors of this article describe the history and philosophy of the original AAR, debunk three myths about the practice that impede its proper use, and finally suggest three improvements that can help business leaders make the most of it.
Keywords: Collaboration and teams; Crisis management; Project management